Impact of asset intensity and other energy-associated CO2 emissions drivers in the Nigerian manufacturing sector: A firm-level decomposition (LMDI) analysis - Fidelis I. Abam; Oliver I. Inah; Bethrand N. Nwankwojike (Heliyon, 2024)
The study considered the impacts of asset intensity and other energy-associated CO2 emissions drivers in the Nigerian manufacturing sector from 2010 to 2020. The Logarithmic Mean Divisia Index (LMDI) was used to explore the driving factors of CO2 emissions: asset intensity, economic output, economic structure, energy intensity, energy mix, and carbon emission coefficient. From the results, the CO2 emissions decreased from 7.49 MtCO2 in 2010 to 3.22 MtCO2 in 2020. Furthermore, among the emissions drivers, the energy mix effect increased CO2 emissions by 0.50 MtCO2, followed by asset intensity (0.29 MtCO2) and economic structure (0.11 MtCO2). The energy intensity, economic output, and emission coefficient effects inhibited CO2 emissions by −4.64 MtCO2, −0.42 MtCO2, and −0.01 MtCO2 respectively. The contribution of the subsectors' emissions shows that the Other Manufacturing subsector emitted 14.62 MtCO2, while Chemical and Pharmaceutical emitted 14.61 MtCO2, Food, Beverages and Tobacco, 7.55 MtCO2, Textile, Apparel, and Footwear, 6.63 MtCO2, Basic Metal and Iron and Steel, 5.15 MtCO2, Plastic and Rubber Products, 2.99 MtCO2, Agro-Allied, 2.71 MtCO2, Oil Refining, 2.01 MtCO2, and Pulp and Paper Products, 1.76 MtCO2. The results indicated that the effect of asset intensity on emission growth is significant and should not be overlooked. Likewise, the effects of CO2 emission drivers were found to impact differently across the subsectors. The latter suggests that firm-specific indicators in the respective subsectors should be one of the primacies during policy development since the driving factors of CO2 emissions fluctuate across the subsectors.